Design of Skewed Connections - Kloiber, Larry; Thornton, William A. (Engineering Journal, 2001)
Skewed connections result when members frame to each other at an angle other than 90 degrees. This paper provides some guidance in the choice of connection, based on safety and economy, and discusses some of the design considerations required for these connections. The standard connection details assume that the members being connected frame at right angles to each other. In most structures there will be some members, which do not meet at right angles. These are referred to as skewed connections. They require special design considerations to provide for safety while providing an economic structure